DESIGNING E-FILING INFORMATION SYSTEM WITH MICROSOFT ACCESS BASED AT PT. USAHA GEDUNG MANDIRI - Zubaidah Hanum; Iwan Kesuma Sihombing; Halimah Tusakdiah (Sean Institute, 2022)
Company or organization needs a good archive system to keep the information or data from lost and easier to find anytime. It aims to make decisions and also becoming evidence and proof if there is problem and it could be made as management responsibility. This study aims to produce an information system for incoming and outgoing mails in Microsoft Access based which can operate mails information system at PT Usaha Gedung Mandiri. In Microsoft Access, we can design,create and manage database easily and fast. This information system design was made because of an unfinished problem in this company related to mails information system that was still traditional so that it encounter delays in giving the information. Furthermore, we can choose application program, mail information system design and design the information system used and then checking and test the design. The product of this application was an information system application with Microsoft office based which can easier and shorten time of users or employee in managing the data, saving incoming and outgoing mails, then provide mail information more effectively and efficiently.